2016
DOI: 10.1007/s12603-016-0670-9
|View full text |Cite
|
Sign up to set email alerts
|

The associations of C-reactive protein with serum levels of polyunsaturated fatty acids and trans fatty acids among middle-aged men from three populations

Abstract: With the exception of consistent inverse association of CRP with total n-6 FAs, there are considerable variations across the three populations in the associations of CRP with different FAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, inclusion criteria differed between the two cohorts, allowing for the inclusion of some individuals with a history of DOI: 10.4236/fns.2018.96054 707 Food and Nutrition Sciences cardiometabolic diseases in the US cohort but not the Japanese. Since the differences we observed have been reported in larger cohorts [27], our findings were unlikely to have been affected by these limitations.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, inclusion criteria differed between the two cohorts, allowing for the inclusion of some individuals with a history of DOI: 10.4236/fns.2018.96054 707 Food and Nutrition Sciences cardiometabolic diseases in the US cohort but not the Japanese. Since the differences we observed have been reported in larger cohorts [27], our findings were unlikely to have been affected by these limitations.…”
Section: Discussionmentioning
confidence: 53%
“…Our findings of the inverse associations of the serum total n-6 PUFA or LA with CRP are supported by several previous epidemiological observations, 11,[13][14][15][16][17][18][19][20] although some epidemiological studies have not found associations 8,9,21 or inverse associations have been found only in the subgroup analyses. 10,22 There is also evidence from randomized trials that even very large changes in LA intake do not substantially affect circulating AA concentrations 30 and do not increase inflammation markers. 7 Similarly, AA supplementation has not had an impact on inflammation markers, 31,32 not even with several fold higher doses (1.5 g/d) compared to typical dietary intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Although several epidemiological studies have evaluated the associations of the n-6 PUFAs with inflammation markers, the findings have been heterogeneous. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Use of circulating PUFAs would remove the bias associated with dietary assessment methods and would also make it possible to investigate the associations of the mainly endogenously produced n-6 PUFAs, gamma-linolenic acid (GLA) and dihomo-gamma-linolenic acid (DGLA). However, only few studies have investigated the associations of GLA or DGLA with inflammation, again with heterogeneous results.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive TFA intake is also assumed to induce abnormal glucose metabolism 11,23,24 and elevated inflammatory biomarkers. 25,26 But while mean HbA1c increased in patients with higher elaidic acid, no significant difference was noted in elaidic acid quartiles. In addition, serum hs-CRP was not associated with elaidic acid level.…”
Section: Discussionmentioning
confidence: 91%